Amplitude-Integrated EEG in the Newborn - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Th value of amplitude-integrated electroencephalography (aEEG) in the newborn is explored by researchers at Washington University, St Louis; Wilhelmina Children's Hospital, Utrecht, Netherlands; and Uppsala University Hospital, Sweden.